2001
DOI: 10.1079/phn2001126
|View full text |Cite
|
Sign up to set email alerts
|

The potential contribution of increased vegetable and fruit consumption to health gain in the European Union

Abstract: Background: The risk of many important diseases can be reduced by consuming a diet rich in vegetables and fruit. For this reason the World Health Organization (WHO) recommends a daily intake of more than 400 g person 21 . The pattern of both the supply and intake of vegetables and fruit and the potential health gain achieved by increasing intake in the European Union (EU) and three accession countries are presented in this paper. Methods: Patterns of supply and dietary intake were assessed using (1) FAO food b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 30 publications
2
44
0
3
Order By: Relevance
“…Among the various mechanisms proposed to explain the ISO-induced cardiac damage, generation of highly cytotoxic free radicals through the auto-oxidation of the drug has been proposed as one of the important causative factors 4 . The consumption of diets rich in plant foods is associated with reduced risk of CVD, and this has been observed in numerous epidemiological studies 5 .…”
Section: Isoproterenolmentioning
confidence: 87%
“…Among the various mechanisms proposed to explain the ISO-induced cardiac damage, generation of highly cytotoxic free radicals through the auto-oxidation of the drug has been proposed as one of the important causative factors 4 . The consumption of diets rich in plant foods is associated with reduced risk of CVD, and this has been observed in numerous epidemiological studies 5 .…”
Section: Isoproterenolmentioning
confidence: 87%
“…Many studies support the value of dietary pattern analysis and some focus on the relationship of overall dietary patterns to health risk (2,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). In fact cardiovascular disease and cancer have a substantial dietary basis, and estimates suggest that better eating habits -for instance, increasing the intake of vegetables and fruits -could result in considerable improvements in public health (45)(46)(47)(48). Newby et al (27), in a study of dietary patterns and corresponding changes in body mass index (BMI) and waist circumference, concluded that consuming a diet that is high in fruit, vegetables, reduced-fat dairy products, and whole grains while low in red and processed meat, fast food, and soda was associated with smaller gains in BMI and waist circumference.…”
Section: Dietary Patternmentioning
confidence: 99%
“…This procedure was done using SAS version 8.1 See Table 5. Dairy desserts (pudding, custard, cheesecake, ice cream) 3 (6) Other dairy products (yogurt) 4 (7) Cheese 5 (2) Lowfat and lowfat products 6 (3,11) Butter, cream, sour cream 7 (4,12,14) Processed fat products (margarine, non-dairy creamer) 8 (13) Oils, cooking oils, and salad dressings 9 (9,53) Nuts and seeds, peanut butter 10 (15, 16) Citrus fruits, natural citrus fruit juices 11 (17,18) Non-citrus fruits and natural non-citrus fruit juices 12 (20) Orange vegetables (not sweet potatoes) 13 (21) Dark green, leafy vegetables 14 (22) Tomatoes and tomato products 15 (24,25,28) Starchy vegetables (potatoes, sweet potatoes, plantain) 16 (23,57) Other vegetables (onions, chilis, peppers) 17 (26,27) Legumes (beans, lentils, garbanzos, soy products) 18 (29) Eggs 19 (31,32,33) Red meat 20 (30) Poultry 21 (35) Seafood and fish 22 (36) Liver and organ meats 23 (34) Processed meat (sausage, bacon) 24 (37) Cakes, cookies and pies 25 (38,39) Breakfast cereals 26 (42,46) Tortillas, tacos, and corn products 27 (40,41) Wheat products 28 (45) Pasta 29 (43,44,58) Grain products, rice, supplements 30 (47) Chips and processed snacks 31 (48) Pizza and other Italian dishes 32 (19,49,50) F...…”
Section: Assessment Of Dietary Patterns and Cluster Analysismentioning
confidence: 99%
“…31 Because price is an important factor influencing food consumption choices, potential regulatory interventions include subsidies for people on low incomes to purchase vegetables and fruit. 32 Incentives can also be provided for industry to improve local access to good-quality products at affordable prices, especially in low-income neighbourhoods where private transport may be unavailable. 32 Such policy interventions could potentially increase consumption beyond the amount modelled here.…”
Section: Discussionmentioning
confidence: 99%
“…32 Incentives can also be provided for industry to improve local access to good-quality products at affordable prices, especially in low-income neighbourhoods where private transport may be unavailable. 32 Such policy interventions could potentially increase consumption beyond the amount modelled here.…”
Section: Discussionmentioning
confidence: 99%